Transcriptomic Characterization of a Synergistic Genetic Interaction during Carpel Margin Meristem Development in Arabidopsis thaliana - Wynn, April N.; Rueschhoff, Elizabeth E.; Franks, Robert G. (PLOS ONE, 2011)
In flowering plants the gynoecium is the female reproductive structure. In Arabidopsis thaliana ovules initiate within the developing gynoecium from meristematic tissue located along the margins of the floral carpels. When fertilized the ovules will develop into seeds. SEUSS (SEU) and AINTEGUMENTA (ANT) encode transcriptional regulators that are critical for the proper formation of ovules from the carpel margin meristem (CMM). The synergistic loss of ovule initiation observed in the seu ant double mutant suggests that SEU and ANT share overlapping functions during CMM development. However the molecular mechanism underlying this synergistic interaction is unknown. Using the ATH1 transcriptomics platform we identified transcripts that were differentially expressed in seu ant double mutant relative to wild type and single mutant gynoecia. In particular we sought to identify transcripts whose expression was dependent on the coordinated activities of the SEU and ANT gene products. Our analysis identifies a diverse set of transcripts that display altered expression in the seu ant double mutant tissues. The analysis of overrepresented Gene Ontology classifications suggests a preponderance of transcriptional regulators including multiple members of the REPRODUCTIVE MERISTEMS (REM) and GROWTH-REGULATING FACTOR (GRF) families are mis-regulated in the seu ant gynoecia. Our in situ hybridization analyses indicate that many of these genes are preferentially expressed within the developing CMM. This study is the first step toward a detailed description of the transcriptional regulatory hierarchies that control the development of the CMM and ovule initiation. Understanding the regulatory hierarchy controlled by SEU and ANT will clarify the molecular mechanism of the functional redundancy of these two genes and illuminate the developmental and molecular events required for CMM development and ovule initiation.